Gender Agitation and Anti-Sexual Harassment : A Study of Kuntowijoyo's Prophetic Social Perspectives - Perdana Putra Pangestu (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
Sexual harassment and violence seems to be a taboo subject and its resolution has not been holistically understood in our society. The fame of the case that never stops surfacing in the public eye, forms a collective massive agitation to crush the naughty sexual paradigm. The author is interested in examining how the construction of movements and counter-narratives are formed in realizing fundamental freedom and understanding related to sexual harassment. The author uses a descriptive qualitative approach using secondary data from literature. The description of the study will be obtained through optimizing the formulation of the topic interpretation surrounding the issue of sexual harassment. The elaboration of interpretation and data that was carried out was then analyzed through Kuntowijoyo's Social Prophetic theoretical lines. This research concludes that the various forms of agitation that are exposed are exposures in building humanization and liberation values for all people in a fair and safe manner. The idea in the form of agitation is a form of invitation for all groups to be involved in efforts to uphold human rights, freedom and security in the public space.